Tumor Heterogeneity: An Important Determinant for Efficacy and Safety in Nanoparticle Anticancer Gene Therapy. Issue 5 (May 2018) - Suresh, P.K.
Abstract : Models of tumor heterogeneity should mimic perfusion in the tumor mass and consider cancer stem cell hierarchy and convertibility. Other important factors include epigenomic alterations, enhanced permeation and retention effects, and the reticuloendothelial system. New stimuli-responsive delivery systems, active targeting-based methods, and corona characterization strategies can deliver genes more precisely.